Photochromic Ionic Hydrogen-Bonded Organic Frameworks for Enhancing Proton Conductivity via Precise Regulation of Photogenerated Radicals - Liu, Cheng; Cao, Li-Hui; Zhou, Zi-Ye; Chen, Xu-Yong; Zhang, Wenmin (ACS applied materials & interfaces, 2025)
Stimulus-responsive hydrogen-bonded organic frameworks (HOFs) have garnered significant attention due to their unique structural tunability and functional diversity, showcasing remarkable application potential. Herein, we propose a photoinduced electron transfer (PIET) strategy to construct photochromic HOFs. Specifically, we successfully prepared two ionic HOFs (iHOF-38 and iHOF-39) with excellent photochromic properties through the solvent slow diffusion method, using bis(benzene-m-sulfonic acid)-naphthalenediimide (m-H2BSNDI) as the organic acid ligand and skillfully employing charge-assisted hydrogen bonding by combining two different organic base ligands. Under 100 °C and 98% RH, iHOF-38 generated radical anions centered around NDI upon UV irradiation, achieving a proton conductivity photoswitching ratio of 2.06. In contrast, iHOF-39 generated dual free radicals under photoinduced action due to the acid–base ligand containing photoresponsive groups (NDI and viologen), and its synergistic effect enhanced the proton conductivity, resulting in a 3.73-fold increase. The aforementioned results indicate that by ingeniously integrating photochromic properties with proton conduction properties and precisely regulating the number of photogenerated radicals, significant improvements in varying degrees of proton conduction performance can be achieved.